Fair Revenue Sharing Mechanisms for Strategic Passenger Airline Alliances - Çetiner, Demet. (Lecture Notes in Economics and Mathematical Systems, 2013)
A major problem arising in airline alliances is to design allocation mechanisms determining how the revenue of a product should be shared among the airlines. The nucleolus is a concept of cooperative game theory that provides solutions for allocating the cost or benefit of a cooperation. This work provides fair revenue proportions for the airline alliances based on the nucleolus, which assumes a centralized decision making system. The proposed mechanism is used as a benchmark to evaluate the fairness of the revenue sharing mechanisms, where the alliance partners behave selfishly. Additionally, a new selfish revenue allocation rule is developed that improves the performance of the existing methods.